PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN AKHLAKUL KARIMAH PESERTA DIDIK - Siti Nurmilah; Fahmi Irfani (Rihlah Review: Jurnal Pendidikan Islam, 2024)
This study aims to determine the role of Islamic religious education teachers in improving the akhlakul karimah students at SMA Negeri 05 Bogor City. Based on the author's initial observations, at SMA Negeri 05 Bogor City, symptoms were found in the field, including: 1) There were students who had not applied morals in daily life in accordance with Islamic teachings. 2) There are students who lack discipline and violate school rules. 3) There are students who do not maintain good manners during learning. 4) There are still students who do not carry out Islamic teachings when interacting socially. And 5) there are still students who do not present their identity as good Muslims. The method used in this research is descriptive qualitative. data collection procedures by way of observation, interviews and documentation, then analyzed the data by providing an explanation of the role of Islamic religious education teachers in improving student morals. motivators and evaluators.